2021
DOI: 10.3390/ijerph18126543
|View full text |Cite
|
Sign up to set email alerts
|

Mental Well-Being or Ill-Being through Coaching in Adult Grassroots Sport: A Systematic Mapping Review

Abstract: There is convincing evidence on the effects of sport and exercise on mental health and well-being. Less evidence is provided about how to achieve these benefits in the context of grassroots sport coaching. We systematically reviewed the scientific literature of three databases to narratively synthesize the current knowledge about which coaching-related factors influence well-being or ill-being, and how to promote mental health in adult athletes through sport coaches. The review includes 52 studies with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 96 publications
1
4
0
Order By: Relevance
“…Athletes' insights, as explored in this study, highlight the significance of AI technologies in influencing coaching relationships, enhancing performance, and shaping training experiences. This is in line with previous research that emphasizes the need to understand athletes' perceptions to effectively integrate technology into sports coaching (Barrio et al, 2021;Fan et al, 2023;Gleaves & Lang, 2017). The athlete narratives gathered in our study revealed a nuanced view of AI's role in sports, reflecting both the opportunities and challenges presented by these technologies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Athletes' insights, as explored in this study, highlight the significance of AI technologies in influencing coaching relationships, enhancing performance, and shaping training experiences. This is in line with previous research that emphasizes the need to understand athletes' perceptions to effectively integrate technology into sports coaching (Barrio et al, 2021;Fan et al, 2023;Gleaves & Lang, 2017). The athlete narratives gathered in our study revealed a nuanced view of AI's role in sports, reflecting both the opportunities and challenges presented by these technologies.…”
Section: Discussionsupporting
confidence: 89%
“…Athlete perspectives are paramount in evaluating the impact and utility of AI-driven coaching technologies. Research has consistently underscored the importance of athletes' views on various facets of their training environment, including coaching relationships, autonomy, motivation, and susceptibility to burnout (Barrio et al, 2021;Chao et al, 2022;Fan et al, 2023). These elements are integral to an athlete's experience and performance and, as such, are critical considerations for the successful implementation of AI technologies in sports coaching.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional treatments for depression typically involve medication and psychotherapy, which can be effective but are not universally accessible or tolerable [26][27][28][29][30][31][32]. A wealth of research indicates that exercise can improve symptoms of depression and promote overall physical and mental well-being [33][34][35][36][37][38]. Studies have shown that exercise can reduce the risk of developing depression and anxiety disorders [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these three psychological needs drive the development and maintenance of athlete motivation, both intrinsic and extrinsic, as well as adaptive outcomes. Finally, the three components of behavioral determinants that support coach autonomy are the coach's orientation, the constructive context, and the athlete's actions and desires (Rato Barrio et al, 2021). Empirical research reminds trainers to use motivation control strategies.…”
Section: Discussionmentioning
confidence: 99%